Late Antique—Early Byzantine urban transformation in Mid-Northern Anatolia: A multiproxy approach from Pompeiopolis - Melis Uzdurum; Mustafa Nuri Tatbul; Susan Marie Mentzer (PLoS ONE, 2026)
During the 6th century CE, many Late Antique cities in the eastern Mediterranean—especially in Anatolia—underwent major changes. By the 7th century CE, most had gradually lost their urban functions. As populations declined, urban spaces were reused for domestic, industrial and rural purposes. This shift is visible in the archaeological record, through the abandonment and reuse of public spaces. At Zımbıllı Tepe-Pompeiopolis, located in in Paphlagonia (northern Anatolia), which was occupied during Late Antiquity and Medieval periods, architectural remains, artifacts, and radiocarbon (C14) dates from both public and private areas show patterns consistent with this broader urban transformation across Anatolia between the 6th and late 7th centuries. To better understand how the site transformed over time, we conducted micro-scale, multiproxy analysis. These included macrobotanical and microdebris studies, micromorphology, x-ray fluorescence (XRF), microscopic fourier transform infrared (micro-FTIR), and C14 dating, based on samples from a street sewer and a connected private latrine. Together, these datasets reveal the cultural and natural processes that shaped the site’s last occupation, its abandonment, and its post-abandonment transformation. The disuse and infilling of the sewer suggest a halt in public maintenance toward the end of the occupation, while the latrine’s earlier abandonment reflects gradual organizational changes already in the 6th century. This study provides a macro-and-micro-scale view of urban transformation during the 6th–7th centuries using a multiproxy approach, which remains rare in archaeological studies of this period in Anatolia.